If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(6 + x) = 2(x + -5) (6 * 3 + x * 3) = 2(x + -5) (18 + 3x) = 2(x + -5) Reorder the terms: 18 + 3x = 2(-5 + x) 18 + 3x = (-5 * 2 + x * 2) 18 + 3x = (-10 + 2x) Solving 18 + 3x = -10 + 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. 18 + 3x + -2x = -10 + 2x + -2x Combine like terms: 3x + -2x = 1x 18 + 1x = -10 + 2x + -2x Combine like terms: 2x + -2x = 0 18 + 1x = -10 + 0 18 + 1x = -10 Add '-18' to each side of the equation. 18 + -18 + 1x = -10 + -18 Combine like terms: 18 + -18 = 0 0 + 1x = -10 + -18 1x = -10 + -18 Combine like terms: -10 + -18 = -28 1x = -28 Divide each side by '1'. x = -28 Simplifying x = -28
| 8y+-x^2=22 | | 1-m/m/m-1/m | | 25/15=n/1.2 | | 2x*2x=1 | | x-1=8x-10 | | -3+4/-5=x | | -1/k+5=18/17k | | -3-4-(-5)=x | | 7(x+4)=20-x | | -3+4+-5=x | | 3+4x=23-x | | 3r+9s=36 | | 3(x-3)=3x+13 | | 4w+5=17 | | 48=(3x+2)(x+4) | | x-2(5x-1)=-6 | | m-3/4=-4/3 | | 5(3x-4)=25 | | 15-2x+11=39 | | 3(9x+15)+13=-77 | | 4(5x-6)=16 | | 7+x-15=-2/3 | | 3(x-9)=12 | | 7n-5(2)=2n-14 | | 1/2(b-8)=4 | | 6-x-5=-5 | | 8x-1=4(2-3x) | | 3(x+1)=39 | | 3x=3/4 | | 6x+5=10+5x | | 7(2x+9)+14=119 | | 3/5x+5y=20 |